Rite of Passage - Løyche, Hans (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2022)
“Rite of Passage” describes a court case raised by an android/artificial intelligence who wishes to apply for citizenship but can only do so if recognized as a human. Among others, the case exposes the vague definition of the term “human”, and the trouble of supplying evidence of sentience or consciousness even in humans. The ethical problems involved in the story can be ascribed to many actual events, among them the recent debate on splicing monkey and human DNA for the sake of producing hybrids with organs suitable for transplantation. The story also touches upon ethical conflicts with regards to endangered wildlife, global warming, media exploitation, commodification, and labor unions.